Infections associated with mesh repairs of abdominal wall hernias: Are antimicrobial biomaterials the longed-for solution?. (June 2018) - Guillaume, O.; Pérez-Tanoira, R.; Fortelny, R.; Redl, H.; Moriarty, T.F.; Richards, R.G.; Eglin, D.; Petter Puchner, A.
Abstract: The incidence of mesh-related infection after abdominal wall hernia repair is low, generally between 1 and 4%; however, worldwide, this corresponds to tens of thousands of difficult cases to treat annually. Adopting best practices in prevention is one of the keys to reduce the incidence of mesh-related infection. Once the infection is established, however, only a limited number of options are available that provides an efficient and successful treatment outcome. Over the past few years, there has been a tremendous amount of research dedicated to the functionalization of prosthetic meshes with antimicrobial properties, with some receiving regulatory approval and are currently available for clinical use. In this context, it is important to review the clinical importance of mesh infection, its risk factors, prophylaxis and pathogenicity. In addition, we give an overview of the main functionalization approaches that have been applied on meshes to confer anti-bacterial protection, the respective benefits and limitations, and finally some relevant future directions.